A case study of quality management practice in rubber based company in Malaysia - Othman, Siti Norezam; Mansor, Mohd Fitri; Harun, Mohd Sani; Abdul Ghani, Zain Ali; Abu, Noor Hidayah (2010)
Quality is one of most important element in every organization in the world. It requires proper management in order to ensure the products met the customer’s standards. Failure to manage and resolve the quality issues will cause many negative impacts towards organization performance. Thus, the aim of the paper is to analyse the quality management, quality activities and initiatives, issues and solutions pertaining to the quality matters in one of rubber based company. Based upon interview session with relevant personnel’s in the company, the solution and recommendation are proposed.